2022
DOI: 10.3390/gels8030168
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Polysaccharide-Based Hydrogels: Rheological and Texture Properties and Ibuprofen Release

Abstract: Polysaccharides are attractive gelling agents in pharmacy due to their safety, biocompatibility, biodegradability, relatively easy way of preparation, and low price. Due to their variable physical-chemical properties, polysaccharides have potentialities to be used for designing new drug delivery systems for controlled drug release. In this comparative study, rheological and texture properties as well as the in vitro release of model drug ibuprofen (IBU) with 11 polysaccharide-based hydrogels were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Xanthan gum is an anionic polysaccharide biopolymer derived from microorganisms [ 59 ]. It is produced by the fermentation activity of the Gram-negative bacteria Xanthomonas campestris under aerobic conditions in a sterile environment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xanthan gum is an anionic polysaccharide biopolymer derived from microorganisms [ 59 ]. It is produced by the fermentation activity of the Gram-negative bacteria Xanthomonas campestris under aerobic conditions in a sterile environment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shear thinning, non-Newtonian behavior, and enhanced elasticity have also been demonstrated for terpolymeric hydrogels consisting of XG, poly(acrylic acid), and poly(N-isopropyl acrylamide) by applying some rheological models such as Bingham, modified Bingham, and Ostwald power laws [ 44 ]. A complex study evaluated the rheological and texture properties of different types of hydrogels comprised of neutral (hydroxy/alkylcelluloses), anionic (carboxyalkylcellulose and its sodium salt, tragacanth, carrageenan, XG), or cationic (CS) polysaccharides designed for drug delivery applications [ 45 ]. It was concluded that the in vitro release of the encapsulated drug significantly varied due to the different viscoelastic properties and to the contribution of the interactions occurring within the polysaccharide-based hydrogels [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…A complex study evaluated the rheological and texture properties of different types of hydrogels comprised of neutral (hydroxy/alkylcelluloses), anionic (carboxyalkylcellulose and its sodium salt, tragacanth, carrageenan, XG), or cationic (CS) polysaccharides designed for drug delivery applications [ 45 ]. It was concluded that the in vitro release of the encapsulated drug significantly varied due to the different viscoelastic properties and to the contribution of the interactions occurring within the polysaccharide-based hydrogels [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum rheological properties contribute to easy mixing, spreading and injection, retention on the skin, packing and removal from containers, and so forth. Besides, it was found that the viscosity of hydrogels may affect drug delivery and the skin penetration of incorporated actives 31,32 . Another aspect is the ability of the hydrogel composites to control drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was found that the viscosity of hydrogels may affect drug delivery and the skin penetration of incorporated actives. 31,32 Another aspect is the ability of the hydrogel composites to control drug release. It is clear that the controlled release promotes increasing efficiency and safety of drug formulations.…”
mentioning
confidence: 99%